Recent Developments of Electrochemical Promotion of Catalysis in the Techniques of DeNOx - Xiaolong Tang; Xianmang Xu; Honghong Yi; Chen Chen; Chuan Wang (The Scientific World Journal)
Electrochemical promotion of catalysis reactions (EPOC) is one of the most significant discoveries in the field of catalytic and environmental protection. The work presented in this paper focuses on the aspects of reaction mechanism, influencing factors, and recent positive results. It has been shown with more than 80 different catalytic systems that the catalytic activity and selectivity of conductive catalysts deposited on solid electrolytes can be altered in the last 30 years. The active ingredient of catalyst can be activated by applying constant voltage or constant current to the catalysts/electrolyte interface. The effect of EPOC can improve greatly the conversion rate of NOx. And it can also improve the lifetime of catalyst by inhibiting its poisoning.